Implementation Of Digital Literacy Program At The Library And Archives Service Of East Kalimantan Province - Andi Sri Yusnani Yasin; Cathas Teguh Prakoso; Santi Rande (UNIVERSITAS PAKUAN, 2026)
The purpose of this study is to examine and analyze the implementation of the Digital Literacy Program at the Library and Archives Service of East Kalimantan Province, as well as to identify and analyze the supporting and inhibiting factors in its implementation. The research employs a qualitative approach with data collection techniques that include in-depth interviews, observation, and document study. The results of the study indicate that the implementation of the digital literacy program has been carried out effectively through various activities such as digital literacy training, internet network access provision, and digital content development. The main supporting factors for the program’s success include local government support, the availability of competent human resources, and adequate infrastructure and facilities. However, there are still challenges, such as limited technological literacy among some community members and the need to enhance program sustainability. Overall, the implementation of the digital literacy program at the Library and Archives Service of East Kalimantan Province has made a significant contribution to improving the community’s ability to access, understand, and utilize digital information intelligently and responsibly.